2018
DOI: 10.14710/nmjn.v7i2.13889
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Islamic Based Caring Practice in Intensive Care Unit: A Qualitative Study

Abstract: Background: Even the advanced technology of modalities in intensive care unit (ICU) has been required a lot, it is important to date that nurses understand the Islamic faithbased healing in the holistic nursing care. Purpose: A phenomenological approach was conducted to describe the caring behaviors based on Islam for the patients in ICU from the perspective of nurses and patients' family. Methods: Fourteen ICU nurses and 10 families participated in the study. In-depth interviews with nurses and families were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 16 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…A trusted relationship based on understanding and respect gained from the stroke patients and family was paramount in enhancing the capacity of the stroke patients to self-care for their recovery. It was reported that a good nurse-client relationship is crucial to help the clients meet their healthcare needs [46], optimize the sense of recovery [24,47], and harmonize body-mind-spirit [21] for stroke patients. In the present study, caring was initially overlooked by the nurses in the clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A trusted relationship based on understanding and respect gained from the stroke patients and family was paramount in enhancing the capacity of the stroke patients to self-care for their recovery. It was reported that a good nurse-client relationship is crucial to help the clients meet their healthcare needs [46], optimize the sense of recovery [24,47], and harmonize body-mind-spirit [21] for stroke patients. In the present study, caring was initially overlooked by the nurses in the clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…The nurse participants have learnt that the caring incorporating yoga was easy, practical and did not burden their workload as their prior thought. Instead, caring could be rewarding and ful lling [48], the nurses felt proud and satis ed by the positive responses and health outcomes of the patients as well as the uplift of nurse profession that was also reported by previous studies [21,24,25]. Therefore, caring is the central concept of nursing which also facilitates to established relationship and trust that resulted in capacity to self-care caring to self and the patients, and nally achieved expected health outcomes in the patients in acute phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A trusted relationship based on understanding and respect gained from the stroke patients and their families was paramount in enhancing the capacity of the stroke patients to self-care for their recovery. It was reported that a good nurse-client relationship is crucial to help the clients meet their healthcare needs [46], optimize the sense of recovery [24,47], and harmonize body-mind-spirit [21] for stroke patients. In the present study, caring was initially overlooked by the nurses in the clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Caring is the main essence of nursing that manifests in nurses' actions and behaviors through building a nurse-patient relationship [20]. Researchers claimed that the concepts of caring and spiritual practice, if paired together, act as a powerful tool that has the potential to create good caring relationship among nurse, patient and patient's family [21]. Through caring relationship, active communication, information [22] and caring atmosphere were created that promote self-care ability, con dence, coping and holistic wellbeing of patients [23], which facilitates healing process even in a critical stage of illness [21,24,25].…”
Section: Introductionmentioning
confidence: 99%